Analysis of PAI Teacher Strategies in Implementing PAI Learning in the Independent Learning Curriculum at SDN Candi Burung 2 Pamekasan - Nailatur Rizqiyah; Masti Yanto (Jurnal Ilmiah Literasi Indonesia, 2025)
The learning strategies used by teachers are an important factor in determining learning success. The aim of this research is to find out PAI teachers' strategies in implementing PAI learning in the independent learning curriculum at SDN Candi Burung 2 Pamekasan. This paper uses a qualitative method with a descriptive type. The subjects of this research are PAI teachers. The data collection method used in this research is through interviews. Meanwhile, the results of this research can be concluded that the PAI teacher's strategy in implementing PAI learning in the independent curriculum at SDN Candi Burung 2 Pamekasan goes through three stages, namely the planning, implementation and evaluation stages. At the planning stage, the steps taken by PAI teachers include: formulating and compiling learning tools, designing learning methods, determining learning tools and materials, and paying attention to the availability of learning facilities. Meanwhile, at the implementation stage, PAI teachers go through several steps, namely initial activities and core activities. Meanwhile, at the evaluation stage, PAI teachers carry out formative and summative evaluations. In the process of implementing this strategy PAI teachers face a number of obstacles. However, PAI teachers were able to overcome these obstacles with various efforts.